Combination of frustra shapes with cross sections and trigger circles for crash box design to absorb energy - Ahmad Yunus, Nasution; Mohd Ruzaimi, Mat Rejab; Siregar, J. P.; Ma, Quanjin (Elsevier Ltd, 2023)
Crash box that has not been maximal in absorbing energy during collisions are the basis for researchers to redesign crash box. There are three designs of crash box that combined frustra, cross section with three holes. This is a novel design that is expected to absorb more energy and minimize deformation and also buckling. The finite element simulation shows that the square model can absorb higher energy than the other two models, that is 142.66 KJ at 0.005 s, a force of 5728 KN, and displacement of 57 mm. Therefore, the recommended shape from this research is the square model.